Protective effects of Xanthohumol against diabetic nephropathy in a mouse model - Fenglin Li; Jinling Zhang; Le Luo; Jing Hu (Karger Publishers, 2023)
Introduction: Diabetic nephropathy (DN) is a long-term loss of renal function occurring in the diabetic patients, leading to 5 million deaths in 2015, and this number is dramatically growing annually. Due to unsatisfied outcome of current treatment, there is urgent need to develop more effective therapeutic drugs for DN. Methods: Approximately 150 kinds of natural small molecule drugs that have been used on the market or in the clinical trials in the presence of high glucose were tested individually on the same batch of human renal glomerular endothelial cells (GECs) and human kidney 2 (HK-2) cells with triplicated wells by using a robotic pipetting workstation to screen for the potential drug candidate. Cell viability and oxidative stress were examined in the GECs and HK-2 cells. DN mouse model was established and treated with 25 mg/kg Xanthohumol. Results: By measuring cell viability, Xanthohumol was selected as our predicted drug candidate for DN because it could mostly protect renal cells from high glucose with about 90% survived GECs and HK-2 cells, about 2.12- and 2.37-fold increase compared to glucose group which was with 42.78% and 37.69% survived GECs and HK-2 cells, respectively. Then, Xanthohumol inhibited high glucose-induced oxidative stress through nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway in vitro. Moreover, Xanthohumol (25 mg/kg) significantly decreased the levels of serum creatinine, blood urea nitrogen, urea protein and kidney weight/body weight ratio in DN mice. In addition, the increase of reactive oxygen species production, and the decrease of superoxide dismutase and catalase activities in DN mice were partially reversed by Xanthohumol. mRNA levels of Nrf2, Hmox1, Nqol genes were all decreased by Xanthohumol DN mice. Discussion/Conclusion: Xanthohumol could ameliorate DN-related impairments via Nrf2 signaling pathway, which might serve as a promising drug candidate for treatment of DN.